IMPLEMENTASI PROYEK PENGUATAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PEMBENTUK PENDIDIKAN KARAKTER DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Arzfi, Bima Prakarsa; Montessori, Maria; Rusdinal, Rusdinal (Dharmas Education Journal (DE_Journal), 2024)
In this study, qualitative methods were used to see how the Pancasila Student Profile Strengthening Project (P5) was implemented at SDN 33 Sawahan to create independent curriculum character education. After being collected through observation, interviews, and documentation, the data were analyzed through preparation, verification, and reduction. The study shows that the implementation of P5 includes design, management, assessment, evaluation, and follow-up. With data literacy, digital, and humanism modules, the theme of P5 is Building body and soul and a sustainable lifestyle. Team formation, introduction to school readiness, character dimension determination, theme determination, and time allocation are all part of P5 management. Formative and summative evaluations are used to evaluate student character development. Meanwhile, evaluation includes finding strengths and monitoring skills. Furthermore, P5 focuses on character strengthening through the Let's Act program. This program functions as a tool and positive habit to improve student character according to the Pancasila student profile. This study provides a comprehensive analysis of the use of P5 as a character education strategy at SDN 33 Sawahan. It provides an example and inspiration for other schools that want to implement P5 to improve their students' character education.